Association of Diabetes with Meningitis Infection Risks: A Systematic Review and Meta-Analysis - Moses Asori; Ali Musah; Razak M. Gyasi (Hindawi - Cambridge University Press, 2022)
Background. The Global Burden of Disease Study in 2016 estimated that the global incident cases of meningitis have increased by 320,000 between 1990 and 2016. Current evidence suggests that diabetes may be a prime risk factor for meningitis among individuals, including older adults. However, findings of prior studies on this topic remain inconsistent, making a general conclusion relatively difficult. This study aimed to quantitatively synthesize the literature on the risk of meningitis associated with diabetes and compare the risk across different global regions. Method. Literature search and study design protocol followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The search was conducted in PubMed, Web of Science, African Journal Online, and Google Scholar using relevant MESH terms. A random effect model was used to pull effect sizes. Results. Initial search yielded 772 papers but 756 studies were excluded due to duplicity and not meeting inclusion criteria. In all, 16 papers involving 16847 cases were used. The pulled effect size (ES) of the association between diabetes and meningitis was 2.240 (OR = 2.240, 95% CI = 1.716-2.924). Regional-base analysis showed that diabetes increased the risk of developing meningitis in Europe (OR = 1.737, 95% CI = 1.299-2.323), Asia (OR = 2.192, 95% CI = 1.233-3.898), and North America (OR = 2.819, 95% CI = 1.159-6.855). These associations remained significant in the study design and etiological classe-based subgroup analyses. However, we surprisingly found no studies in Africa or South America. Conclusion. Diabetes is a risk factor for developing meningitis. Given that no research on this topic came from Africa and South America, our findings should be contextually interpreted. We, however, encourage studies on diabetes-meningitis linkages from all parts of the world, particularly in Africa and South America, to confirm the findings of the present study.